Study on Embedded Sacrificial Anode Anti-Corrosion Technology for Existing Reinforced Concrete Structures - YANG Weilai, ZHAO Rongxin, CHEN Ning, WU Huayong, XU Ning (Cailiao Baohu)
In order to address the poor applicability of existing embedded sacrificial anodes in existing reinforced concrete structures，a new type of embedded sacrificial anode applicable to existing reinforced concrete structures was developed.Indoor simulation tests were conducted to investigate the changes in steel reinforcement potential，current，and current density，as well as the corrosion product diffusion behavior of the embedded sacrificial anode in simulated concrete pore solution and in concrete components subjected to chloride salt attack.Results showed that in simulated concrete pore solution，the embedded sacrificial anode was able to fully polarize the steel reinforcement within 6 h.During the service period，the steel reinforcement potential consistently remained more negative than－780 mV，without exceeding the hydrogen evolution potential.In concrete components，the embedded sacrificial anode achieved 80%polarization of the steel reinforcement within 6 h.A single anode provided a stable output current of 0.4 mA，with a current density of 12.74 mA/m2.As the distance between the embedded sacrificial anode and the steel reinforcement measurement point increased，the polarization degree of the steel reinforcement decreased，resulting in a reduced protective effect.The maximum protection distance was determined to be 80 cm.The corrosion products of the anode exhibited diffusive behavior and were distributed as fine white particles within the mortar pores，which could reduce the risk of concrete cracking caused by the expansion of corrosion products.